PENGARUH UKURAN, LIKUIDITAS, PROFITABILITAS, STRUKTUR MODAL, DAN MANAJEMEN RISIKO TERHADAP NILAI PERUSAHAAN - Grecia Stefani; Agustin Ekadjaja (Jurnal Paradigma Akuntansi, 2023)
This research is aimed to find empirical evidence about the impact of firm size, liquidity, profitability, capital structure, and enterprise risk management on firm value in all manufacturing sector consumer goods industry that listed in Indonesian Stock Exchange period of 2017 until 2020. Samples that were used in this study as 84 data based on purposive sampling. The software that used in this research is SPSS version 25. The result of this study indicates that firm size and liquidity has a positive and does not have a significant effect on the firm value, profitability and capital structure has a positive and significant effect on the firm value, enterprise risk management has a negative and does not have a significant effect on the firm value.